Implementation of Land Sale Regulation in Pasuruan District: Pelaksanaan Peraturan Penjualan Tanah di Kabupaten Pasuruan - Pratama , Ilham Muhammad Jalu; Phahlevy , Rifqi Ridlo (Indonesian Journal of Public Policy Review, 2025)
General Background: Land regulation plays a crucial role in ensuring legal certainty over ownership and transfer of land rights in Indonesia. Specific Background: Government Regulation Number 24 of 1997 mandates that every land sale and purchase transaction must be conducted before a Land Deed Official (PPAT) through an authentic deed. However, rural communities in Pasuruan District still practice land transactions using Village Sale and Purchase Statements (SPJB/SKJB), which raises questions about their legal standing. Knowledge Gap: Previous studies have not fully examined the practical coexistence of formal legal frameworks with local customary administrative practices. Aims: This study aims to analyze the implementation of PP No. 24/1997 and assess the legal effectiveness of SPJB/SKJB in land registration processes at the local level. Results: The findings show that several villages continue issuing SPJBs, while the National Land Agency (BPN) only recognizes them if issued before 1997. Novelty: The study reveals persistent local practices that adapt legal frameworks to administrative convenience, reflecting the gap between regulation and social reality. Implications: The research contributes to understanding policy implementation challenges in rural land governance and the need for harmonization between legal norms and community practices. Highlights: Persistent informal land transaction practices in rural Pasuruan. Limited legal recognition of village-issued sale documents. Need for alignment between state law and community land practices. Keywords: Land Registration, PP 24/1997, Sale and Purchase Deed, PPAT, Village Administration